Analysis of the Influence of Business Ethics in Accounting: Case of Ethical Violation at PT Garuda Indonesia - Sipahutar, Bela Putri Saqina; Rahwani, Diba Ameilia; Zebua, Dwi Fadhillah Apriliana; Nasirwan, Nasirwan (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of business ethics in accounting practices, focusing on cases of ethical violations occurring in Indonesia. Business ethics is considered a fundamental element in maintaining integrity and public trust in financial reports. This study examines how ethical principles play a crucial role in accounting practices. Through literature analysis and real cases, such as the PT Garuda Indonesia (Persero) Tbk scandal in 2018, this research highlights the impact of ethical violations on the credibility of financial reports and public trust. The PT Garuda Indonesia case demonstrates how financial report manipulation and improper revenue recognition can damage the company's reputation and the integrity of the accounting profession. The study concludes that strict adherence to ethical codes and effective oversight are essential to prevent ethical violations and ensure transparency and accuracy in financial reporting. These findings are expected to provide insights and recommendations for improving ethics in accounting practices in the future.